Implementasi Business Process Improvement Menggunakan Pendekatan Lean Management - Devinta Nurul Fitriana; Indri Sudanawati Rozas; Noor Wahyudi (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2021)
A business process is a structured collection of interrelated activities or work within an organization to produce a product or service. For the quality of products and services, of course, an effective and efficient business process is needed. So far, many business processes are still depicted in the form of still images in the form of flowcharts, because they do not know the notation called BPMN (Business Process Model and Notation) which can create images of business processes as well as model them in a simulation. By using BPMN, the most effective and efficient business processes can be simulated to produce organizational products or services. This research implements BPI (Business Process Improvement) with lean management method, and DMAIC framework (Define, Measure, Analysis, Improve, Control). DMAIC is used for gradual improvement of business processes. The tools used to assist DMAIC in this research include the SIPOC diagram (Supplier, Input, Process, Output, Customer), identification of CTQ (Critical to Quality), measuring process capability using DPMO (Defects Per Million Opportunities), root cause analysis, then simulated using the Bizagi Modeler tool. From research on STAI Attanwir's business processes, it was found that out of 46 business processes there were 15 that experienced waste. Of the 7 types of waste, at STAI Attanwir there are 2 wastes that occur, namely waiting waste and movement waste. Of the 15 As-Is and To-Be business processes that experienced waste, after a simulation using BPI, the results showed that 12 business processes experienced significant changes in terms of time and resources. However, there are 3 business processes whose utilization level remains abnormal even though improvements have been made.